2006
DOI: 10.1517/17425255.2.4.591
|View full text |Cite
|
Sign up to set email alerts
|

The road map to oral bioavailability: an industrial perspective

Abstract: Optimisation of oral bioavailability is a continuing challenge for the pharmaceutical and biotechnology industries. The number of potential drug candidates requiring in vivo evaluation has significantly increased with the advent of combinatorial chemistry. In addition, drug discovery programmes are increasingly forced into more lipophilic and lower solubility chemical space. To aid in the use of in vitro and in silico tools as well as reduce the number of in vivo studies required, a team-based discussion tool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(103 citation statements)
references
References 97 publications
3
99
0
Order By: Relevance
“…One method to improve tumor imaging is to improve the bioavailability 31 of the dye conjugate. A piperazine unit is common in many drugs, 32 so we incorporated a piperazine linker with the goal of increasing bioavailability 33 of the dye conjugate.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…One method to improve tumor imaging is to improve the bioavailability 31 of the dye conjugate. A piperazine unit is common in many drugs, 32 so we incorporated a piperazine linker with the goal of increasing bioavailability 33 of the dye conjugate.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…This is due to the larger numbers of highly-absorbed compounds amongst the marketed drugs that constitute the datasets 7,8 . compounds with low absorption due to solubility issues 11 . Imbalanced datasets are a problem for modelling.…”
Section: Introductionmentioning
confidence: 99%
“…10 It has been observed that several agents enhance the bioavailability of these drugs, which in turn increase their therapeutic potential. 11,12 In the present study, pharmacokinetics profile of paclitaxel was explored specially emphasizing in the pre-treatment with curcumin which causes inhibition of CYP3A4 and P-gp activities.…”
Section: Resultsmentioning
confidence: 99%